Rational thinking under costly information: macroeconomic implications - Gomes, O. (2012)
The notion of optimized rational behavior in the formation of expectations is used in this note to study the dynamics of a simple macroeconomic model. In a setting where departures from stability are not possible under perfect foresight, the selection of an optimal degree of rationality may lead to the generation of long-term endogenous fluctuations.